The loss of interest (of the child) when born by surrogate motherhood - Sales Pallarés, Lorena (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The contradictions that the development of assisted reproduction techniques provoke in the legal systems have in the surrogacy its maximum exponent. Technological maternity has not been accompanied by adequate legal regulation, which has caused the Courts and the DGRN to coexist in a duality that irremediably causes the loss of the best interests of the child. After closing the doors to the registration of the filiation of minors born through surrogacy, the Supreme Court pointed to adoption as a way to protect the interests of minors. However, recent court decisions do not seem to indicate that this is the fastest or most appropriate course of action. Therefore, we have reviewed different approaches that the SC has accepted in analogous issues seeking a justification or a way out of these situations. Recognition out of complacency or attenuated public order are some of the options explored in view of the current refusal to face the social demand for a fair and adequate regulation for all those affected.
Keywords: surrogacy; best interests of the child; intended parents; forum shopping; attenuated public order; human dignity